Effects of Resistance Exercise and Nutritional Supplementation on Dynamic Cerebral Autoregulation in Head-Down Bed Rest - Kermorgant, Marc; Nasr, Nathalie; Custaud, Marc-Antoine; Navasiolava, Nastassia; Arbeille, Philippe; Guinet, Patrick; Labrunée, Marc; Besnier, Florent; Arvanitis, Dina N.; Czosnyka, Marek; Senard, Jean-Michel; Pavy-Le Traon, Anne (Frontiers in Physiology, 2019)
Head-down bed rest (HDBR) is commonly considered as ground-based analog to spaceflight and simulates the headward fluid shift and cardiovascular deconditioning associated with spaceflight. We investigated in healthy volunteers whether HDBR, with or without countermeasures, affect cerebral autoregulation (CA). Twelve men (at selection: 34±7 years; 176±7 cm; 70±7 kg) underwent three interventions of a 21-day HDBR: a control condition without countermeasure (CON), a condition with resistance vibration exercise (RVE) comprising of squats, single leg heel and bilateral heel raises and a condition using also RVE associated with nutritional supplementation (NeX). Cerebral blood flow velocity was assessed using transcranial Doppler ultrasonography. CA was evaluated by transfer function analysis and by the autoregulatory index (Mxa) in order to determine the relationship between mean cerebral blood flow velocity and mean arterial blood pressure. In RVE condition, coherence was increased after HDBR. In CON condition, Mxa index was significantly reduced after HDBR. In contrast, in RVE and NeX conditions, Mxa were increased after HBDR. Our results indicate that HDBR without countermeasures may improve dynamic CA, but this adaptation may be dampened with RVE. Furthermore, nutritional supplementation did not enhance or worsen the negative effects of RVE. These findings should be carefully considered and could not be applied in spaceflight. Indeed, the subjects spent their time in supine position during bed rest, unlike the astronauts who perform normal daily activities.